PERUBAHAN STRUKTUR DAN KEPADATAN TRIKOMATA NON GLANDULER SERTA LUAS DAUN KAKAO (Theobroma cacao L.) PADA PERLAKUAN STRES KEKURANGAN AIR - Prihastanti, Erma; T, Soekisman; Soepandi, Didie; Qayim, Ibnul (JURNAL SAINS DAN MATEMATIKA, 2009)
ABSTRACT–Cacao is the one important crop in Indonesia. Water stress is perhaps the major factor limiting crop growth. Plant responses to water stress include morphological of biochemical changes. This reserch was aimed studying strtructure and density of non glanduler trichomes, and leaf area on cacao leaves on drought experiment. The drought studies used throughfall displacment experiment (TDE). The result show that cacao leaves have non glanduler trichomes type stellat. Non Glanduler trichomes were distributed throughtout the vein of leaves with distribution in abaxial parts of the leaves. TDE give non significant effect to trichomes density and Ieaf area. The highest trichomes happened on March 2008 6.9861/cm2. Leaf area on shade Ieaves (273,56 cm2) more higher than sun leaves (235,50 cm2). Keyword : Trichomes non glanduler, cacao leaves, leaf area